THE SEMANTIC ANALYSIS OF PHRASEOLOGICAL UNITS WITH ANTHROPONYMIC COMPONENTS IN THE ENGLISH AND UZBEK LANGUAGES - Goyibov, Umarjon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Phraseological units are an assemblage of two or more word constituents with a unique and often figurative meaning, including as patient as Job, a silver lining, crooked as a corkscrew in English, and Har kim oʻz aybini bilsa Vali boʻladi, boʻzchining mokisidek, teshik munchoq yerda qolmas in Uzbek. There is a growing trend among scientists in the study of phraseological units with certain subtypes of onomastic components from the viewpoint of modern approaches, such as cognitive and linguocultural perspectives. Phraseological units with onomastic components are regarded as precise manifestations of the cultural background of a certain nation. They are directly connected with human knowledge about history, literature, culture, religion, folklore, legends, and geography, which all constitute the encyclopedic wealth of the language. With regard to human’s encyclopaedic data, the onomastic component of phraseological units manifests a distinct comprehensive cultural, historical, literary, political, social, and religious information related to such components. The article aims to analyse phraseological units with an anthroponymic component as one of the onomastic constituents from the semantic viewpoint in which they are based on the meaning construction and the encyclopaedic information about anthroponyms participated in such units. It has been defined that the motivation of the semantics of phraseological units with its anthroponymic component in non-related languages, especially English and Uzbek, has not been studied sufficiently. The article discusses the semantic peculiarities of anthroponymic components in the system of phraseological units in compared languages. The conclusion is that the meaning of phraseological units with anthroponymic components is associated with anthroponyms’ personalities, activities, physical and psychological conditions, and their influence on other objective phenomena.